1990
DOI: 10.1113/expphysiol.1990.sp003467
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic stimulation causes increased output of lymphocytes from the popliteal node in anaesthetized sheep

Abstract: SUMMARYStimulation of the lumbar sympathetic chain at a frequency of 4 Hz caused a threefold increase in the lymphocyte output in efferent lymph from the popliteal node in anaesthetzed sheep. The increase was accounted for by a rise in both lymph flow and lymphocyte count. Intra-arterial infusion of phentolamine (10 sg kg-1 min-l) abolished the nerve-mediated increases in flow and cell count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…The data in the literature are seemingly in conflict, which may be illustrated with just two examples. Stimulation of the sympathetic outflow leads to increased outflow of lymphocytes from popliteal lymph nodes (McHale and Thornbury, 1990), which may be classified as activation of the immune system. On the other hand, sympathectomy has been reported to enhance immune responses (Besedovsky et al, 19881, which may be interpreted as indicating an inhibitory action of the nervous system on the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The data in the literature are seemingly in conflict, which may be illustrated with just two examples. Stimulation of the sympathetic outflow leads to increased outflow of lymphocytes from popliteal lymph nodes (McHale and Thornbury, 1990), which may be classified as activation of the immune system. On the other hand, sympathectomy has been reported to enhance immune responses (Besedovsky et al, 19881, which may be interpreted as indicating an inhibitory action of the nervous system on the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…58 Confirming a neural involvement in this effect, stimulation of the sympathetic chain prompted an increase in lymphocyte and lymph output from the node. 60 These experimental findings suggest that there is control of leucocyte retention and/or trafficking through this sympathetic neural pathway. Although peripheral lymphatic vessels are little more than an endothelial cell monolayer, larger collecting lymphatic vessels often contain a layer of lymphatic smooth muscle along with connective tissue and nerve terminals, which enable contractility to the point where the lumen can transiently disappear, 61 propelling lymph along the vessels.…”
Section: Effects Of Anaesthetics and Vasoactive Mediators In Leucocytmentioning
confidence: 96%
“…This could have a role in reducing nodal capacitance or it could be implicated in the lymphocytosis that occurs when sympathetic nerves are activated. McHale and Thornbury [95] showed that lymphocyte output from the popliteal node of the anesthetized sheep was increased almost threefold in response to stimulation of the sympathetic chain at 4 Hz (Fig. 14).…”
Section: Physiology Of Lymph Nodesmentioning
confidence: 96%
“…Thus Horstmann [100,101] suggested that initiation of lymphatic [95] contractions and their propagation are purely mechanical events. He argued that the functional pumping unit of a guinea-pig mesenteric lymph duct was the segment between two valves, since smooth muscle was scant or absent in the valvular region.…”
Section: Regulation Of Lymph Flowmentioning
confidence: 99%